2022
DOI: 10.3389/fped.2021.800331
|View full text |Cite
|
Sign up to set email alerts
|

Food Hypersensitivity in Children Aged 0–3 Years of the Lviv Region in Ukraine: A Cross-Sectional Study

Abstract: Aim: To determine the prevalence and to estimate factors associated with food hypersensitivity in young children of the Lviv region in Ukraine.Methods: A prospective cross-sectional survey study was conducted between 2016 and 2017 in the Lviv region of Ukraine. A specially designed questionnaire about food hypersensitivity of young children developed and validated by M. J. Flokstra-de Blok was used after translation into the Ukrainian language. The questionnaire included 34 questions, grouped into general and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…After duplicates were removed, the titles and abstracts of 1,628 reports were reviewed by one of the authors (JFL), and 131 met the eligibility criteria (Figure 1). The current review was primarily based on 107 full papers, 2‐108 but, due to the scarcity of data, we also chose to cite five relevant abstracts 109‐113 for a more complete picture of child health in Ukraine. Our literature search was limited to papers published in English.…”
Section: Methodsmentioning
confidence: 99%
“…After duplicates were removed, the titles and abstracts of 1,628 reports were reviewed by one of the authors (JFL), and 131 met the eligibility criteria (Figure 1). The current review was primarily based on 107 full papers, 2‐108 but, due to the scarcity of data, we also chose to cite five relevant abstracts 109‐113 for a more complete picture of child health in Ukraine. Our literature search was limited to papers published in English.…”
Section: Methodsmentioning
confidence: 99%
“…A number of nutritional, environmental, and socio-economic factors influence the chemical composition of breast milk during lactation, including the stage of lactation, gestational age at delivery, maternal diet, and maternal metabolic diseases such as diabetes [ 39 , 40 ]. Numerous studies have shown that the mothers’ diet and health can greatly affect the fatty acid content of breast milk [ 41 , 42 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Little information is known about the prevalence of food allergies in Ukraine. In a 2022 cross-sectional study on food hypersensitivity in children aged 0–3 years of the Lviv region, the most common allergens were milk, egg, and wheat [ 36 ]. Ukraine enacted a law in August 2019 regarding food products labeling, including imported foods.…”
Section: Resultsmentioning
confidence: 99%